Synthesis of cubic zirconium(IV) nitride, c-Zr3N4, in the 6–8 GPa pressure region. Issue 16 (November 2019) - Taniguchi, Takashi; Dzivenko, Dmytro; Riedel, Ralf; Chauveau, Thierry; Zerr, Andreas
Abstract: We report on the lowermost pressure and temperature conditions where cubic zirconium(IV) nitride having Th3 P4 -type structure, c-Zr3 N4, forms in a belt-type apparatus. This novel hard material having exceptional wear resistance by machining of low-carbon steels appears at pressures between 6.5 and 7.7 GPa when heated to 1400–1600 °C. Single-phase samples were obtained at P  = 7.7 GPa thus indicating that the industrial scale synthesis of this innovative material is feasible. Chemical reaction of the sample material with the Pt-capsule led to formation of a Pt–Zr alloy, as a minor admixture, which can potentially be used as a binder for cementing of polycrystalline c-Zr3 N4 tools.